Corruption, Governmental Activities, and Markets - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1994)
Paper discusses the factors that contribute to the spread of corruption as well as the implications of corruption for markets and for public sector activities. It is argued that corruption can be contained mainly by a scaling down of the public sector activities that stimulate its growth.